2023
DOI: 10.3390/nu15163500
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition and Associated Factors in Older Patients with Rheumatoid Arthritis: A Cross-Sectional Study

Abstract: Objective: To describe the frequency of malnutrition in older patients with rheumatoid arthritis (RA) and investigate associated risk factors. Methods: This multicenter, cross-sectional study included participants aged ≥65 years who met the 2010 ACR/EULAR criteria for RA. Nutritional status was assessed using the Mini Nutritional Assessment Short Form (MNA-SF) and based on variables, such as albumin level, the Geriatric Nutritional Risk Index (GNRI), and vitamin D. Data were also collected on epidemiological v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Our study found a significant manifestation of nutritional deficiency in patients with RA. The results of previous studies also support this finding [47,48]. In a study focusing on older RA patients, Cano-Garcia et al found that one-third of older RA patients have impaired nutritional status [48].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our study found a significant manifestation of nutritional deficiency in patients with RA. The results of previous studies also support this finding [47,48]. In a study focusing on older RA patients, Cano-Garcia et al found that one-third of older RA patients have impaired nutritional status [48].…”
Section: Discussionmentioning
confidence: 70%
“…The results of previous studies also support this finding [47,48]. In a study focusing on older RA patients, Cano-Garcia et al found that one-third of older RA patients have impaired nutritional status [48]. RA patients are at risk of nutritional deficiency due to fatigue, pain, loss of motor function, and nausea, which could result in the reduction of food consumption and consequently the decreased intake of vitamins and minerals [49].…”
Section: Discussionmentioning
confidence: 78%
“…These two factors have different roles depending on age and sex, and both vitamin D and the gut microbiome seem to play a role in the development of immunotolerance, especially at younger ages. This implies that hypovitaminosis D and dysbiosis may be relevant in the genesis of the vast majority of immune-mediated diseases, which develop mainly in younger patients [49,58], while with age they may have a main role as mediators of disease severity, leading the immune system to a more inflammatory phenotype if they are altered [105].…”
Section: Discussionmentioning
confidence: 99%
“…From a pathophysiological point of view, in older adults with vitamin D deficiency, there are increased levels of markers of inflammation that can potentially spill over into immunemediated diseases [104]. This is the case of what appears to be happening in RA, where in malnourished subjects with reduced levels of vitamin D there is an increased level of inflammation as well as an increase in disease activity [105].…”
Section: Sex and Age Differences In The Role Of Vitamin D And The Gut...mentioning
confidence: 99%
“…The total body weight usually remains stable in RC, despite the reduced lean body mass, which is compensated by an increased fat mass. The excess visceral body fat in RA patients was reported to be associated with an increased risk of hypertension, insulin resistance, and MetS [2,11]. It seems that RC may accelerate morbidity and mortality in patients with RA and is associated with MetS [2].…”
Section: Introductionmentioning
confidence: 99%